Strategic behavior and policy choice on the U.S. Supreme Court - Hammond, Thomas H., 1947- (Stanford University Press, 2005)
Despite several decades of research on Supreme Court decision-making by specialists in judicial politics, there is no good answer to a key question: if each justice's behavior on the Court were motivated solely by some kind of "liberal" or "conservative" ideology, what patterns should be expected in the Court's decision-making practices and in the Court's final decisions? It is only when these patterns are identified in advance that political scientists will be able to empirically evaluate theories which assert that the justices' behavior is motivated by the pursuit of their personal policy preferences. This book provides the first comprehensive and integrated model of how strategically rational Supreme Court justices should be expected to behave in all five stages of the Court's decision-making process. The authors' primary focus is on how each justice's wish to gain as desirable a final opinion as possible will affect his or her behavior at each stage of the decision-making process